Direct comparison of solution and solid phase synthesis of sequence-defined macromolecules. Issue 28 (12th June 2019) - Holloway, Joshua O.; Wetzel, Katharina S.; Martens, Steven; Du Prez, Filip E.; Meier, Michael A. R.
Abstract : Sequence-defined macromolecules of high molecular weight are synthesised by the combination of click chemistry with multicomponent reactions. The synthesis is performed on solid phase as well as in solution to directly compare the two approaches. Abstract : The synthesis of perfectly defined, monodisperse macromolecules is one of the challenges faced by polymer chemists today. Such precision synthesis requires a fundamentally different approach to conventional polymer synthesis, but in turn can unlock the door to many new applications. Therefore, we introduce here the combination of ultra-fast "click" reactions using 1, 2, 4-triazoline-3, 5-diones (TAD) with the highly efficient and versatile Passerini three-component reaction. This new approach not only resulted in the synthesis of monodisperse, sequence-defined macromolecules of high purity and molecular weight (>7000 Da), but also offered new insights into the iterative synthesis of sequence-defined macromolecules in general, as we present a detailed comparative study of the same chemistry protocols carried out on solid phase as well as in solution.